PEMAHAMAN GURU PRASEKOLAH RAUDHATUL ATHFAL TENTANG KESIAPAN SEKOLAH ANAK - Syarfina, Syarfina; Yetti, Elindra; Fridani, Lara (Program Studi Magister Pendidikan Anak Usia Dini, 2018)
Preschool teachers including Raudhatul Athfal (RA) teachers have an important role in building children's school readiness. The purpose of this research is to find out to what extend RA teachers’ understanding about children’s school readiness. The research was conducted by using qualitative approaches. Data were collected through questionnaires distributed to all RA teachers in Langsa. The results show that teachers understand school readiness as a child's readiness to continue school based on the age, independence in daily activities, and the ability to write, read and count. Activities implemented by RA teachers in building children's school readiness by playing, singing, and field trips while materials used such as colors, props, cards, and beams. Teachers assessed children’s school readiness by observing daily activities and evaluating of student’s work. Family factors are considered as a major impact on children's school readiness. Recommendation are made in term of findings is planning some intervention to improve teacher's understanding on children's school readiness concept. Keywords: school readiness, children’s shool readiness, preshcool teacher, preparedness program. Guru prasekolah termasuk guru Raudhatul Athfal (RA) memiliki peran penting dalam membangun kesiapan sekolah anak. Tujuan dari penelitian ini adalah untuk mengetahui sejauh mana pemahaman guru RA tentang kesiapan sekolah anak. Metode yang digunakan adalah metode kualitatif. Data dikumpulkan melalui kuesioner yang disebarkan kepada seluruh guru RA di Kota Langsa. Hasilnya menunjukkan bahwa guru memahami kesiapan sekolah sebagai kesiapan anak untuk melanjutkan sekolah berdasarkan usia, kemandirian dalam melakukan aktivitas harian, serta kemampuan dalam hal menulis, membaca dan berhitung. Kegiatan yang dilakukan guru RA dalam membangun kesiapan sekolah anak meliputi bermain, bernyanyi, dan field trip dengan material berupa warna, alat peraga, kartu, dan balok. Guru menilai kesiapan sekolah anak dengan melakukan observasi harian dan evaluasi hasil karya. Faktor keluarga dianggap yang memberi pengaruh besar dalam hal kesiapan sekolah anak. Rekomendasi dari penelitian ini agar adanya tindakan untuk meningkatkan pemahaman guru terhadap konsep kesiapan sekolah anak. Kata kunci: Kesiapan sekolah, Kesiapan sekolah anak usia dini, guru prasekolah, program persiapan.